PENGARUH PERGANTIAN MANAJEMEN, TIPE KAP, OPINI AUDITOR, KESULITAN KEUANGAN PERUSAHAAN, PERSENTASE PERUBAHAN ROA DAN UKURAN PERUSAHAAN TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK - Kikih Sugiarti; Hadi Pramono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
The main purpose of this research is examining the effects of management changes, the type of KAP, auditor opinion, financial distress, change of ROA percentage and firm size to auditor changes. This research was carried out on manufacturing company listed on the Indonesia Stock Exchange (BEI) for the period 2009-2011. The selection of sample using purposive sampling method and get total sample are 84 research data. The analysis of this research used is logistic regression at level significance 5%. Result of this research show that management changes, the type of KAP, auditor opinion, financial distress, change of ROA percentage and firm size do not have significant effect for auditor changes.Keyword: auditor change, management changes, the type of KAP, auditor opinion, financial distress, change of ROA percentage, firm size.